Efficiency and non-Efficiency of Imprisonment in International Criminal Law - Behzad Razavifard (Faṣlnāmah-i Pizhūhish-i Huqūq-i Kiyfarī, 2012)
Imprisonment fundamentally borninthe sphere of National criminallaw. In other word, for many years imprisonment has been viewed anddictated on the base of crime doings inside the borders of the NationStates. Imprisonment has been an excommunicating punishment thatits efficiency harshly criticized in many criminal law systems as a“school of repeating the crime”. But today malfunctions ofthispunishment has been reduced in many ways in the developedcountries by performing reformations in management of prisons, butacceptance of the efficiency of such punishment regarding theInternational crimes has been doubtful. Such a phenomenon can beanalyzed both with the punitive approach andutilitarian approach inpenology. But first of all, the main thing about efficacy of suchpunishment in the sphere of International crimes is suggesting andadopting a suitable degree of the punishment regarding the characterof International criminals. However, the success of such an importanttask depends on organization and establishment of an independentinstitution for administrating the affairs of an International prison. Anindependent institution with special task of International kind ofpunishment must be created and its strong structure must performintimidating,corrective andtreatmentativetasks appropriately. Only inthis way we can hope the great International criminals receiveanappropriate punishment and also potential criminals and guilty beprevented from doing crime